Pengembangan Modul Pembelajaran Kimia Berbasis Praktikum Sederhana Pada Materi Laju Reaksi - Anjani, Surya; Junaidi, Eka; Siahaan, Jeckson (FKIP University of Mataram, 2024)
This research is a Research and Development type with the aims to determine: 1) The characteristic of chemistry learning module based on simple experimental on the rate of reaction subject, and 2) The feasibility and practicality of the chemistry learning module based on simple experimental on the rate of reaction subject. The method used in this research is the 4D (Define, Design, Development, and Dissemination). This research was carried out until the development stage. The population were XI IPA students of SMAN 1 Pringgarata of the academic year 2021/2022. While the sample in this study were55 student who were taken randomly with stratified (stratified random sampling). The result showed that the value of validity obtained using the Aiken index (V) was 0,78 in the category of valid. Meanwhile, practicality of the chemistry learning module developed can be seen from the student responses of 84% in the category of high practicality. Based on the data, it can be conclude that the developed chemistry learning module based a simple experimental on the rate of reaction subject is feasible and practical so that it can be used in the learning process.